1996
DOI: 10.1021/ma950153k
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Small-Angle X-ray Scattering Studies of Spinodal Decomposition Kinetics in a Semidilute Polystyrene−Dioctyl Phthalate Solution

Abstract: Synchrotron-based time-resolved small-angle X-ray scattering was used to measure the early-stage spinodal decomposition kinetics in a highly viscous semidilute solution of polystyrene in dioctyl phthalate. Although strong nonlinearities in the kinetics were observed, a linear theory analysis could fit the evolution of the structure factor at short times and low wavenumbers. Nonlinearities become significant earlier at higher wavenumbers, which is consistent with recent computer simulation studies. From the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…50 The tendency to form clusters increases with increasing solute concentration and with decreasing temperature. Similar inhomogeneities were also observed in SAXS measurements on moderately concentrated polystyrene solutions in dioctylphthalate 51 and in cyclohexane. 52 The slow mode was also observed by Burchard 53 and Brown et al 54 Although the origin of this mode is not fully understood, it may reflect an association between chains.…”
Section: Figuresupporting
confidence: 79%
“…50 The tendency to form clusters increases with increasing solute concentration and with decreasing temperature. Similar inhomogeneities were also observed in SAXS measurements on moderately concentrated polystyrene solutions in dioctylphthalate 51 and in cyclohexane. 52 The slow mode was also observed by Burchard 53 and Brown et al 54 Although the origin of this mode is not fully understood, it may reflect an association between chains.…”
Section: Figuresupporting
confidence: 79%
“…Although further careful studies are required, this suggests the relevance of a two-fluid model. Similar analysis may also be applied to the early stage of phase separation of polymer systems [153][154][155].…”
Section: 12mentioning
confidence: 99%
“…Although Okano et al 17 and others 18 have found full agreement with the O-Z behavior, experiments carried out in the semidilute regime of polymer solutions have shown deviations from the Ornstein-Zernike function. An "excess scattering" has been reported at low wavenumbers from polymeric solutions 1,[19][20][21][22][23][24] which is caused by the enhanced long wavelength concentration fluctuations in the system. It is not clear so far as to what causes this excess scattering.…”
Section: Theoretical Backgroundmentioning
confidence: 99%